Stochastic Dominance to Account for Uncertainty and Risk in Conservation Decisions. Issue 4 (18th January 2016) - Canessa, Stefano; Ewen, John G.; West, Matt; McCarthy, Michael A.; Walshe, Terry V.
Abstract: Practical conservation normally requires making decisions in the face of uncertainty. Our attitude toward that uncertainty, and the risks it entails, shape the way conservation decisions are made. Stochastic dominance (SD), a method more commonly used in economics, can be used to rank alternative conservation actions by comparing the probability distributions of their outcomes, making progressive simplified assumptions about the preferences of decision makers. Here, we illustrate the application of SD to conservation decisions using the recovery plan for an endangered frog species in Australia as a case study. SD is simple and intuitively appealing for conservation decisions; its broader application may encourage conservation decision makers to consider probabilistic uncertainty in light of their preferences, which may otherwise be difficult to recognize and assess transparently. A better treatment of attitudes towards uncertainty and risk may help ensure rational decision making in conservation and remove potential causes of stakeholder conflict.